The role of interferon regulatory factors in atherosclerosis - Wang, Yingsong; Fang, Tianxiang; Zheng, Xiaoya; Huangfu, Ning (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular diseases (CVDs) remain a leading cause of global morbidity and mortality, largely driven by the progression of atherosclerotic plaques. In atherosclerosis (AS), transcription factors and epigenetic mechanisms play pivotal roles in regulating gene expression. Interferon regulatory factors (IRFs), a family of transcription factors initially identified for their role in coordinating interferon (IFN) responses, are now recognized as critical modulators of innate and adaptive immunity. Emerging evidences highlights their involvement in inflammation, lipid metabolism, cell differentiation, cell proliferation, and programmed cell death during AS pathogenesis. This review synthesizes current knowledge on the roles and regulatory mechanisms of IRFs in AS, offering novel insights and potential therapeutic targets for AS management.